Co-operative learning : the social and intellectual outcomes of learning in groups - Gillies, Robyn M., 1949-; Ashman, A. F. (Adrian F.) (RoutledgeFalmer, 2003)
The contributors to this book, many of whom are recognised world experts on cooperative learning, make insightful links between the theories that underpin the study of group dynamics and their practical application to the classroom.